Preparation and Characterization of Amorphous B Powders by Salt-Assisted SHS Technique - Yujing Ou; Peiqing La; Dandan Zhu; Yalong Zhu (Advances in Materials Science and Engineering)
To use the salt-assisted SHS technique to prepare B powders was proposed. Calculation results found that the adiabatic combustion temperature of the B2O3-Mg reaction system was 2604 K, higher than the 1800 K criterion of self-propagating temperature, which meant that the SHS application was feasible. When 0, 10%, 20%, 30%, 40%, 50%, and 60% NaCl content were added, the adiabatic combustion temperature of the reaction system decreased linearly. When 60% NaCl content was added, the adiabatic combustion temperature was 1799 K (lower than 1800 K), unsuitable for self-propagating reaction, which was consistent with the experimental results. Through scanning electron microscope (SEM), energy disperse spectroscopy (EDS), and particle size analysis, the influence of different addition of NaCl on the morphology, average particle size, and purity of prepared B powder was investigated. EDS and chemical analysis indicated that the purity of prepared B powder was over 96% and the average particle size was within the range of 0.4~0.8 μm when the content of NaCl was 50%. The analysis of X-ray diffraction (XRD) and selected area electron diffraction (SAED) proved that the prepared B powder was amorphous.